Checklist for standardized reporting of drug-drug interaction management guidelines - Floor-Schreudering, A; Geerts, A; Aronson, J; Bouvy, M; Ferner, R; De Smet, P (2014)
Purpose: Inconsistencies and omissions in drug-drug interaction (DDI) management guidelines may lead to harm and suboptimal therapy. The purpose of this study was to define a checklist for DDI management guidelines to help developers produce high-quality guidelines that will support healthcare providers in clinical practice. Methods: We carried out a two-round Delphi process with an international panel of healthcare providers, most of whom are pharmacists involved in providing DDI information, in order to select those items that should be addressed in DDI management guidelines (including grading systems that could be used). Results: Twenty-three panellists reached consensus on 19 items in two main domains. These were consolidated into a checklist of 15 elements for standardized reporting in management guidelines. For each element a description is provided to specify what information should be documented in that specific element. Conclusions: It was possible to reach a broad consensus on which relevant items should be included in a checklist for the development of DDI management guidelines. © 2013 Springer-Verlag Berlin Heidelberg.